(untitled) (The Pakistan Development Review, 2005)
I am extremely grateful to Pakistan Institute of Development Economics, Islamabad for giving me an opportunity to share my views on “Skill Development for Growth and Productivity”. Pakistan is currently experiencing an exciting period of economic and social change. The post-WTO regime and the global market dictate has exposed Pakistans’ economy to international competitiveness necessitating rapid technological changes in the industry. There is definite and recurring need to optimise human resources through Skill Development efforts for achieving high productivity culture for investments in the industrial, commercial, agriculture and services sectors. There is clear indication that low cost labour will no longer be significant advantage for any business which is not based on productivity charged and quality oriented workforce. Therefore, a growing realisation exists for the huge skill deficiency and the demand for competitive workforce with constant supply from educational, vocational/technical training institutions. These hard facts point towards urgent development of strong network between various stakeholders to achieve skill development for economic development. Indeed skill excellence and human resource development has been acknowledged as the major component of economic and social development that contributes in direct proportion to poverty alleviation and national prosperity.